FOXD1 Repression Potentiates Radiation Effectiveness by Downregulating G3BP2 Expression and Promoting the Activation of TXNIP-Related Pathways in Oral Cancer - Lin, Che-Hsuan; Lee, Hsun-Hua; Chang, Wei-Min; Lee, Fei-Peng; Chen, Lung-Che; Lu, Long-Sheng; Lin, Yuan-Feng (Cancers, 2020)
Radiotherapy is commonly used to treat oral cancer patients in the current clinics; however, a subpopulation of patients shows poor radiosensitivity. Therefore, the aim of this study is to identify a biomarker or druggable target to enhance the effectiveness of radiotherapy on oral cancer patients. By performing an in silico analysis against public databases, we found that the upregulation of FOXD1, a gene encoding forkhead box d1 (Foxd1), is extensively detected in primary tumors compared to normal tissues and associated with a poor outcome in oral cancer patients receiving irradiation treatment. Moreover, our data showed that the level of FOXD1 transcript is causally relevant to the effective dosage of irradiation in a panel of oral cancer cell lines. The FOXD1 knockdown (FOXD1-KD) dramatically suppressed the colony-forming ability of oral cancer cells after irradiation treatment. Differentially expressed genes analysis showed that G3BP2, a negative regulator of p53, is predominantly repressed after FOXD1-KD and transcriptionally regulated by Foxd1, as judged by a luciferase-based promoter assay in oral cancer cells. Gene set enrichment analysis significantly predicted the inhibition of E2F-related signaling pathway but the activation of the interferons (IFNs) and p53-associated cellular functions, which were further validated by luciferase reporter assays in the FOXD1-KD oral cancer cells. Robustly, our data showed that FOXD1-KD fosters the expression of TXNIP, a downstream effector of IFN signaling and activator of p53, in oral cancer cells. These findings suggest that FOXD1 targeting might potentiate the anti-cancer effectiveness of radiotherapy and promote immune surveillance on oral cancer.